Potential metabolomic biomarkers for the identification and diagnosis of type A acute aortic dissection in patients with hypertension - Hao, Xiao-Bin; Han, Yue; Ni, Er-Ru; Ye, Ming-Cai; Li, Gang; Wu, Xi-Jie; Qiang, Hai-Feng; Zhao, Jun (Frontiers in Cardiovascular Medicine, 2022)
Objectives Most patients with acute aortic dissection (AAD) have a history of hypertension. Diagnosis of AAD in patients with hypertension at an early stage is complicated and challenging. This study aimed to explore the distinctive metabolic changes in plasma samples of AAD patients with hypertension and patients with hypertension only and provide early identification and diagnosis of AAD in patients with hypertension. Materials and methods We collected blood samples from 20 patients with type A AAD and hypertension admitted to the emergency department and physically examined other 20 patients with hypertension as controls. The plasma metabolomic profiles of these patients were determined using untargeted metabolomics with ultra-high-performance liquid chromatography-quadrupole time-of-flight mass spectrometry. Results A total of 38 metabolites that differed between the AAD and hypertension groups were screened. In the positive ion mode, 12 metabolites were different between the two groups, and in the negative ion mode, 26 metabolites were different. Among the 26 different metabolites detected by the negative ion mode, 21 were significantly upregulated and five were downregulated in patients with AAD compared to patients with hypertension. Moreover, five metabolites were upregulated and seven were significantly downregulated in patients with AAD compared to those with hypertension, as detected by the positive ion mode. The metabolites differentially expressed in AAD were mainly involved in lipid metabolism (fatty acid biosynthesis, biosynthesis of unsaturated fatty acids, and linoleic acid metabolism), carbohydrate metabolism (galactose, fructose, and mannose metabolisms), and membrane transport (ATP-binding cassette transporters). Interestingly, plasma hydrocortisone and dimethylglycine concentrations were significantly increased in patients with type A AAD, with the highest area under the curve value (AUC = 0.9325 or 0.9200, respectively) tested by the receiver operating characteristic curve analysis. Conclusion This study provides possible metabolic markers for the early clinical diagnosis of AAD in patients with hypertension.